Investigation on spectroscopy characteristics of different metamorphic degrees of coal-based graphite - Li, Jing; Wang, Lu; Cao, Daiyong (Frontiers in Earth Science, 2024)
To gain insights into the spectroscopy characteristics from coal to graphite, we investigated different metamorphic degrees of coal-based graphite which were collected from Hunan Province China. In this paper, by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and Raman spectroscopy, graphite with different metamorphism degrees has been characterized to explore the evolution of macromolecular structure of organic matter during graphitization. The results show that with the increase of metamorphism degree, the 002-diffraction peak of the series of samples gradually shrinks and narrows, and the peak intensity becomes stronger, indicating that the microcrystalline structure gradually becomes regular and ordered. As the degree of graphitization increase, the uniformity of particle size in coal samples observed gradually increases, and the morphology becomes more regular, transitioning from disordered and irregular shapes to a structured large-scale flake pattern. The crystallinity improves, and the massive coal particles gradually coalesce into large plate crystals, with the inter-particle pores gradually closing. The graphite structure becomes increasingly evident. The FTIR spectra show that as the degree of graphitization increases, the peak at 1,581 cm−1 corresponding to C=C vibrations gradually intensifies. Some inert functional groups are retained throughout the graphitization process. The pores between coal particles gradually close, and the morphology of graphite particles becomes more regular and ordered. Additionally, during the graphitization process, structures similar to carbon nanotubes may develop. Throughout the structural transformation from coal macromolecules to graphite crystals, the size of the sp2 planar domains in single-layer graphene increases, and the lattice structure of carbon atoms gradually enlarges. These findings contribute to a comprehensive understanding of the properties and characteristics of coal-derived graphite, and can provide theoretical reference and basis for the metallogenic mechanism of coal-derived graphite and the efficient utilization of coal.